Human homeodomain-interacting protein kinase-2 (HIPK2) is a member of the DYRK family of protein kinases and maps to chromosome 7q32-q34 - Hofmann, Thomas G.; Mincheva, Antoaneta; Lichter, Peter; Dröge, Wulf (Biochimie, 2000)
Here we identified the human serine/threonine kinase HIPK2 as a novel member of the DYRK kinase subfamily. Alignment of several DYRK family proteins including the kinases minibrain, MJAK, PKY, the Dictyostelium kinase YakA and Saccharomyces YAK1 allowed the identification of several evolutionary conserved DYRK consensus motifs within the kinase domain. A lysine residue conserved between all DYRK kinase family members was found to be essential for the kinase function of HIPK2. Human HIPK2 was mapped to chromosome 7q32-q34 and murine HIPK2 to chromosome 6B, the homologue to human chromosome 7.
Gesehen am 03.02.2021